An algorithm for scene change detection in h.264/avc compressed domain - Nguyen, Quang Duy. (2012)
In this report, an algorithm is proposed to detect scene changes including both abrupt scene changes and gradual scene changes in H.264/AVC compressed domain with a minimal decoding.